IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN CHARACTER EDUCATION THROUGH P5-P2RA ON STUDENTS' LEARNING BEHAVIOR AT MTS CINA - Abdul Hadi (Penelitian dan Pengembangan Ilmu, 2025)
This study discusses the implementation of the independent curriculum that integrates P5-P2RA character learning at MTs Cina and its influence on students' learning behavior. In the context of current national education, the independent curriculum is expected to be able to encourage the development of character, creativity, and independence of students in the learning process. The implementation of the project-based learning model and P5-P2RA character values ​​including believing in God Almighty and having noble character, global diversity, independence, mutual cooperation, critical and creative reasoning are the main focuses in efforts to foster an independent attitude in students. The method used is a qualitative approach with a descriptive design, which includes data collection through observation, in-depth interviews with teachers and students, and documentation studies related to the ongoing learning process. The results of this study indicate that the implementation of the independent curriculum and P5P2RA character learning at MTs Cina is actively able to improve students' independent character, as seen from the high motivation to learn, flexibility in thinking, and the ability to think critically and creatively when solving various learning challenges.